Engineering construction. Part 1, - Warren, William Henry, 1852-1926 (Longmans, Green and Co., 1921)
The third edition of this text is now part 1 as it will be followed by part 2 devoted to masonry and concrete structures.
Previous ed.: published as Engineering construction in steel and timber. 1910.
Includes index.
Keywords: Structural analysis (Engineering); Bridges.; Steel, Structural.; Wooden bridges.; elektronické knihy; electronic books